Bamboo and rattan genetic resources and use: Proceedings of the third INBAR-IPGRI Biodiversity, Genetic Resources and Conservation Working Group Meeting: 24-27 August, 1997, 1PGRI-APO, Serdang: and research reports - Rao, A.N.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (1999)
The working group made notable progress in the period 1995-97: new projects were formulated and carried out by partners in different countries, covering identification of species diversity, patterns of genetic variations between and within the species, identification of ex situ and in situ conservation areas in different countries, seed storage and others. This volume contains a summary of the Proceedings of the Third Meeting of the Working Group, during which research progress was reviewed and new activities planned. It also includes eight reports on IPGRI-supported research work.